Potret Sumber Pendapatan Baru Bagi Korban PHK Pada Masa Pandemi Di Kota Surabaya - Wildan AryaPutra Rosdiyanto; hendry Cahyono (Universitas Negeri Surabaya, 2022)
The Covid-19 pandemic in the East Java region resulted in Termination of Employment (PHK) for employees which caused quite a number of victims to be affected by layoffs. Based on data from the Department of Manpower and Transmigration of East Java Province, the number of victims of layoffs reached 7,246 workers. The prolonged impact of the COVID-19 pandemic has forced many companies to stop operating and thousands of workers were forced to be laid off or have their contracts terminated. The main factor is because the company's burden is quite heavy. Based on this background, this study aims to find out how victims affected by layoffs can adapt and continue their economy. As well as being able to understand and know the adaptation mechanism of laid-off victims in meeting their daily needs and to know explanations and descriptions of social steps for victims after being laidoff due to the Covid-19 pandemic in Surabaya. Furthermore, it is hoped that it can provide information and knowledge on adaptation to social life of layoff victims during the pandemic to meet their daily needs in order to survive in the midst of the Covid-19 condition. The type of research method used is descriptive qualitative. Adaptations made by victims of layoffs due to Covid-19 in the city of Surabaya, namely by saving expenses for daily family needs and victims of layoffs being able to become entrepreneurs by opening their own businesses according to their abilities, experience and relationships. Keywords: Layoff Victims, Economic Growth, Social Adaptation.